Lifetime Risk for Sudden Cardiac Death in the Community. Issue 7 (July 2016) - Bogle, Brittany M.; Ning, Hongyan; Mehrotra, Sanjay; Goldberger, Jeffrey J.; Lloyd‐Jones, Donald M.
Abstract : Background: Sudden cardiac death (SCD) is a leading cause of death in the United States and often occurs without previous cardiac symptoms. Lifetime risk for SCD and the influence of established risk factors on lifetime risks for SCD have not been estimated previously. Methods and Results: We followed Framingham Heart Study participants who were free of cardiovascular disease before their earliest examination. SCD was defined as death attributed to coronary heart disease within 1 hour of symptom onset without another probable cause of death, as adjudicated by a panel of 3 physicians. Lifetime risk for SCD was estimated to 85 years of age for men and women, with death attributed to other causes as the competing risk, and stratified by risk factor levels. We followed 2294 men and 2785 women for 160 396 person‐years; 375 experienced SCD. At 45 years of age, lifetime risks were 10.9% (95% CI, 9.4–12.5) for men and 2.8% (95% CI, 2.1–3.5) for women. Greater aggregate burden of established risk factors was associated with a higher lifetime risk for SCD. Categorizing men and women solely by blood pressure levels resulted in a clear stratification of lifetime risk curves. Conclusions: We present the first lifetime risk estimates for SCD. Greater aggregate risk factor burden, or blood pressure level alone, is associated with higher lifetime risks for SCD. This high risk of premature death attributed to SCD (approximately 1 in 9 men and 1 in 30 women) should serve as a motivator of public health efforts in preventing and responding to SCD.